Multiple sclerosis in First Nations Canadians: A pilot comparison study. (August 2016) - Marrie, Ruth Ann; Hall, Nicholas; Sadovnick, A Dessa
Background: Genetic and clinical characteristics associated with multiple sclerosis (MS) may differ by ethnicity but few studies have evaluated whether characteristics of MS differ between individuals according to First Nations (FN) ethnicity. Objective: Using a cross-sectional observational design, we compared clinical and genetic characteristics between people with MS of FN and non-FN ethnicity. Methods: We recruited participants of FN ethnicity with MS. We conducted a medical records review for each participant followed by a standardized interview and drawing of blood samples. The blood underwent genetic analyses for several HLA alleles. We compared the study sample with 127 non-FN MS participants from another study conducted in the same region using the same data collection procedures. Results: We included 144 participants with MS, of whom 17 (11.8%) self-identified as FN. The age of symptom onset was earlier and the diagnostic delay shorter among FN participants although these differences did not reach statistical significance. As compared to non-FN participants, FN participants with MS had increased odds of comorbid psychiatric disease (OR 5.38; 95% CI: 1.84–15.8), and were less likely to be HLA-DRB1*1501 positive (OR 0.32; 95% CI: 0.11–0.96). Conclusion: Genetic and clinical characteristics of MS differ among Canadians of FN and non-FN ethnicity.